Pretreatment Risk Stratification for Endoscopic Kidney-sparing Surgery in Upper Tract Urothelial Carcinoma: An International Collaborative Study - Foerster, Beat; Abufaraj, Mohammad; Matin, Surena F; Azizi, Mounsif; Gupta, Mohit; Li, Wei-Ming; Seisen, Thomas; Clinton, Timothy; Xylinas, Evanguelos; Mir, M Carmen; Schweitzer, Donald; Mari, Andrea; et al. (European urology, 2021)
BACKGROUND: Several groups have proposed features to identify low-risk patients who may benefit from endoscopic kidney-sparing surgery in upper tract urothelial carcinoma (UTUC). OBJECTIVE: To evaluate standard risk stratification features, develop an optimal model to identify ≥pT2/N+ stage at radical nephroureterectomy (RNU), and compare it with the existing unvalidated models. DESIGN, SETTING, AND PARTICIPANTS: This was a collaborative retrospective study that included 1214 patients who underwent ureterorenoscopy with biopsy followed by RNU for nonmetastatic UTUC between 2000 and 2017. OUTCOME MEASUREMENTS AND STATISTICAL ANALYSIS: We performed multiple imputation of chained equations for missing data and multivariable logistic regression analysis with a stepwise selection algorithm to create the optimal predictive model. The area under the curve and a decision curve analysis were used to compare the models. RESULTS AND LIMITATIONS: Overall, 659 (54.3%) and 555 (45.7%) patients had ≤pT1N0/Nx and ≥pT2/N+ disease, respectively. In the multivariable logistic regression analysis of our model, age (odds ratio [OR] 1.02, 95% confidence interval [CI] 1.0-1.03, p = 0.013), high-grade biopsy (OR 1.81, 95% CI 1.37-2.40, p < 0.001), biopsy cT1+ staging (OR 3.23, 95% CI 1.93-5.41, p < 0.001), preoperative hydronephrosis (OR 1.37 95% CI 1.04-1.80, p = 0.024), tumor size (OR 1.09, 95% CI 1.01-1.17, p = 0.029), invasion on imaging (OR 5.10, 95% CI 3.32-7.81, p < 0.001), and sessile architecture (OR 2.31, 95% CI 1.58-3.36, p < 0.001) were significantly associated with ≥pT2/pN+ disease. Compared with the existing models, our model had the highest performance accuracy (75% vs 66-71%) and an additional clinical net reduction (four per 100 patients). CONCLUSIONS: Our proposed risk-stratification model predicts the risk of harboring ≥pT2/N+ UTUC with reliable accuracy and a clinical net benefit outperforming the current risk-stratification models. PATIENT SUMMARY: We developed a risk stratification model to better identify patients for endoscopic kidney-sparing surgery in upper tract urothelial carcinoma.
Keywords: Humans; Radical nephroureterectomy; karcinom z přechodných buněk; urologické nádory; ledviny; Upper tract urothelial carcinoma; Kidney; lidé; Kidney-sparing surgery; Urologic Neoplasms; Risk stratification; Ureteral Neoplasms; nádory močového měchýře; Retrospective Studies; Carcinoma, Transitional Cell; retrospektivní studie; Risk Assessment; nádory močovodu; Urinary Bladder Neoplasms; hodnocení rizik